ANALISIS BEBAN KERJA DAN KEBUTUHAN PEGAWAI PADA PERUSAHAAN DAERAH PARKIR MAKASSAR RAYA KOTA MAKASSAR - Mariah Mariah; Ridwan Ridwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study is to provide an instrument in the process of institutional restructuring in PD Parkir Raya Makassar, by assessing the workload of Unit, the results of which will be used as the material (input) for land-use planning process / improvement of the organizational structure and staffing. It also aims to obtain information about the efficiency and work performance unit / organizational unit / office holders and their use in order to improve the quality of employees. The scope of work includes the load measurement workload across existing employees within the scope of PD. Parkir Makassar Raya both Organic Employees, Employee Contracts and Employees with research methods using the effective working hours, the hours of work that should be filled with work to produce a good product is concrete or abstract (object or service). The results of this study indicate that PD Parking Makassar Kingdom in 2016 this number workload of 121 945 man hours (OJ), the number of employee needs as many as 87 people, while employees who have as many as 76 people, so the PD Parkir Makassar Raya shortage of staff as 11 people.